SYMPTOMATOLOGY AND MODIFICATIONS IN THE DAILY ROUTINES OF PREMENOPAUSAL WOMEN - Rosiane Pitombeira; Francisca Elisângela Teixeira Lima; Fernanda Jorge Magalhães; Ires Lopes Custódio; Shérida Karanini Paz de Oliveira (Universidade Federal do Paraná, 2011)
The objective of this study was to investigate the changes which happen in women's lives during the premenopause and to check the principle symptoms they refer to. The research was carried out in a Basic Health Unit in the city of Fortaleza in the state of Ceará and the study population consisted of 101 premenopausal women. Data collection was via interview, and the results were analyzed and organized into tables. It was ascertained that the symptomatology associated with premenopause syndrome was highly prevalent, with 92.07% of the women experiencing at least one of the symptoms, most commonly hot flushes, irritability and forgetfulness; respecting the principle alterations in daily life, symptoms linked to depression and to metabolic changes were most referred to, confirming that the premenopausal transition has a large impact on life. The nurse can act with women as a facilitator for confronting and coming to terms with this phase of life.